KARAKTER DAN ETIKA SOSIAL MAHASANTRI DI LINGKUNGAN MA’HAD AL-JAMI’AH UIN RADEN INTAN LAMPUNG - M. Izzad Khairi Yazdi; Septuri; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify, explain, and examine the social ethical values ​​imparted to students, in addition to assessing the social ethical character demonstrated by students at Ma'had UIN Raden Intan. The methodology applied in this study is descriptive qualitative, with a case study approach. The data collection process involved conducting comprehensive interviews with the leadership of the Ma'had, ustadz, administrative personnel, and mahantri, along with engaging in participatory observation of activities occurring within the Ma'had environment. The research findings reveal that: First, the social ethical values ​​internalized at Ma'had UIN Raden Intan Lampung include ethics towards fellow students, administrators, ustadz, leaders, society, the state, and the environment. Second, the social ethical character reflected in the lives of the students includes friendliness, the habit of greeting, the spirit of mutual assistance, tolerance, and respect and obedience to the administrators and ustadz, although some students are still found to be less disciplined in participating in Ma'had activities. Meanwhile, in the community sphere, students demonstrate social concern through social service and active participation in political activities on campus. In addition, environmental and social media ethics are implemented through behaviors that maintain cleanliness (mutual cooperation and picket), as well as wise and polite use of social media.